ASSESSMENT OF LOSSES OF THE ELECTRIC POWER IN THE CONDITIONS OF UNCERTAINTY AS A PART OF ACSKAE - T. T. Omorov; R. N. Kurmanalieva; R. C. Osmonova (Известия высших учебных заведений: Проблемы энергетики)
The task of calculation of losses of the electric power on the distributive electrical networks (DEN) of 0,4 kV is considered. It is supposed that such perturbing factors as asymmetry of currents and tension, unauthorized selections of the electric power in the networks and parametric uncertainties caused by accidental variations of resistance of interpersonal sections of trunk lines because of changes of climatic conditions act on DEN. Application of the known methods of calculation in these conditions leads to difficult computing procedures. The new technique of assessment of technical and commercial losses of the electric power in DEN oriented for creation of the algorithmic and special software of the appropriate subsystem of the automated control system and the accounting of the electric power (ACSKAE) is offered.